Interactive Da’wah Communication of KH. Anwar Zahid on YouTube: Integrating Traditional and Contemporary Methods - Mubasit, Mubasit (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
Preachers need effective communication patterns for their religious messages to be conveyed properly. KH. As a preacher, Anwar Zahid has combined traditional and contemporary communication patterns and created interactive dialogue with his audience. This study aims to identify KH Anwar Zahid's communication patterns on his YouTube platform, focusing on his preaching methods. This research uses a qualitative approach with digital ethnography. Journals, books, electronic documents, and da'wah content analysis are used as research data. Data collection techniques include observation, content analysis, and documentation. Data analysis is done through data reduction, presentation, and conclusion drawing. This research was conducted from June to December 2024. The results of this study show that the integration of traditional preaching and the adaptation of contemporary preaching through the method of dialogue creates religious participation among audiences. He can implement interactive verbal and non-verbal communication in his preaching—the YouTube channel of KH. Anwar Zahid, as a representation of Islamic media, not only conveys religious messages but also facilitates value transformation through communicative-dialogic da'wah methods. This research has implications for da'wah communication patterns in the digital space, positively impacting audience engagement in religious activities.